COVID-19 in a patient with end-stage renal disease on chronic in-center hemodialysis after evidence of SARS-CoV-2 IgG antibodies. Reinfection or inaccuracy of antibody testing. (2020) - Munoz Mendoza, Jair; Alcaide, Maria L.
Highlights: Possible reinfection with SARS-CoV-2 in an ESRD patient with prior positive IgG antibody test against SARS-CoV-2. Potential lack of antibody protection after asymptomatic infection in ESRD patients. The prospect of antibody dependent enhancement. The need for careful interpretation of antibody test in ESRD patients until further understanding of reinfection risk and antibody response. Abstract: A patient with end-stage renal disease on hemodialysis with a previous positive SARS-CoV-2 IgG antibody was diagnosed with severe COVID-19. Issues regarding reinfection, the potential lack of antibody protection after asymptomatic infection, the possibility of antibody dependent enhancement and careful interpretation of antibody test results are discussed.